High-Throughput Identification of Candidate Strains for Biopreservation by Using Bioluminescent Listeria monocytogenes - El Kheir, Sara M.; Cherrat, Lamia; Awussi, Ahoefa A.; Ramia, Nancy E.; Taha, Samir; Rahman, Abdur; Passerini, Delphine; Leroi, Françoise; Petit, Jeremy; Mangavel, Cécile; Revol-Junelles, Anne-Marie; Borges, Frédéric (Frontiers in Microbiology, 2018)
This article describes a method for high-throughput competition assays using a bioluminescent strain of L. monocytogenes. This method is based on the use of the strain L. monocytogenes EGDelux, for which luminescence is correlated to growth. It constitutes an indicator of L. monocytogenes growth in mixed cultures. To this aim, luminescence kinetics were converted into a single numerical value, called the Luminescence Disturbance Indicator (LDI), which takes into account growth inhibition phenomena resulting in latency increase, decrease in the luminescence rate, or reduction of the maximum luminescence. The LDI allows to automatically and simultaneously handle multiple competition assays which is required for high-throughput screening (HTS) approaches. The method was applied to screen a collection of 1 810 strains isolated from raw cow’s milk in order to identify non-acidifying strains with anti-L. monocytogenes bioprotection properties. This method was also successfully used to identify anti-L. monocytogenes candidates within a collection of Lactococcus piscium, a species where antagonism was previously described as non-diffusible and requiring cell-to-cell contact. In conclusion, bioluminescent L. monocytogenes can be used in HTS to identify strains with anti-L. monocytogenes bioprotection properties, irrespectively of the inhibition mechanism.